HIV-2 genomic RNA accumulates in stress granules in the absence of active translation. Issue 20 (28th October 2014) - Soto-Rifo, Ricardo; Valiente-Echeverria, Fernando; Rubilar, Paulina S.; Garcia-de-Gracia, Francisco; Ricci, Emiliano P.; Limousin, Taran; Décimo, Didier; Mouland, Andrew J.; Ohlmann, Théophile
Abstract: During the post-transcriptional events of the HIV-2 replication cycle, the full-length unspliced genomic RNA (gRNA) is first used as an mRNA to synthesize Gag and Gag-Pol proteins and then packaged into progeny virions. However, the mechanisms responsible for the coordinate usage of the gRNA during these two mutually exclusive events are poorly understood. Here, we present evidence showing that HIV-2 expression induces stress granule assembly in cultured cells. This contrasts with HIV-1, which interferes with stress granules assembly even upon induced cellular stress. Moreover, we observed that the RNA-binding protein and stress granules assembly factor TIAR associates with the gRNA to form a TIAR-HIV-2 ribonucleoprotein (TH2RNP) complex localizing diffuse in the cytoplasm or aggregated in stress granules. Although the assembly of TH2RNP in stress granules did not require the binding of the Gag protein to the gRNA, we observed that increased levels of Gag promoted both translational arrest and stress granule assembly. Moreover, HIV-2 Gag also localizes to stress granules in the absence of a 'packageable' gRNA. Our results indicate that the HIV-2 gRNA is compartmentalized in stress granules in the absence of active translation prior to being selected for packaging by the Gag polyprotein.